Factors influencing international tourists’ food preference towards Malaysian local food / Hawaliana Selamat - Selamat, Hawaliana (2013)
In the age of post modernity, the experiences of tourist play an important role in economic and social life. As tourist demand a higher standard in quality services, quality food and hospitality experiences particularly have caught the full attention in tourism industry on one hand and the literature on hospitality on the other. Food has been regarded as not only being a basic necessity for tourist consumption but also as an essential element of regional culture. Local food and beverages have urbanized from being crucial necessity for tourists being recognized as an imperative part of the local culture that tourists consume. Food can at least provide superfluous opportunities for tourist to be in a more memorable and enjoyable holiday atmosphere than they expected, no matter whether trying different kinds of food is the main purpose for tourist to travel. Gastronomy is thus seen as an important source of marketable images and experiences for the tourist. Tourists on a trip are frequently eager for new experiences and willing to take greater risks than in their ordinary life. Indeed, some tourists might suffer from “food neophobia,” a concept which refers to human’s natural tendency suspect new and unfamiliar foods. The trip might stimulate their neophilic tendencies, motivating them to try novel and strange dishes. The implications of the findings are discussed and directions for future research are suggested.